2014
DOI: 10.1056/nejmoa1301824
|View full text |Cite
|
Sign up to set email alerts
|

A Form of the Metabolic Syndrome Associated with Mutations inDYRK1B

Abstract: BACKGROUND Genetic analysis has been successful in identifying causative mutations for individual cardiovascular risk factors. Success has been more limited in mapping susceptibility genes for clusters of cardiovascular risk traits, such as those in the metabolic syndrome. METHODS We identified three large families with coinheritance of early-onset coronary artery disease, central obesity, hypertension, and diabetes. We used linkage analysis and whole-exome sequencing to identify the disease-causing gene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(150 citation statements)
references
References 51 publications
3
146
0
1
Order By: Relevance
“…For many of these families identified to date, the culprit mutation has proved to be a highly damaging mutation within a gene that strongly influences circulating low-density lipoprotein (LDL) cholesterol levels (e.g., familial hypercholesterolemia (FH) genes, including LDLR, APOB, PCSK9, and, less commonly, LDLRAP1, ABCG5, and ABCG8) (29). In more recent studies, the culprit mutation has been found in genes predisposing to severe forms of the metabolic syndrome (e.g., LRP6, DYRK1B) (30,31). The initial observation that supported the highly multigenic nature of CAD for a majority of subjects presenting with CAD was the failure of linkage studies performed on families with a more typical low penetrance of disease to detect any susceptibly loci (29,32).…”
Section: Linkage Studies Fail To Identify Genetic Determinants Of Commentioning
confidence: 99%
“…For many of these families identified to date, the culprit mutation has proved to be a highly damaging mutation within a gene that strongly influences circulating low-density lipoprotein (LDL) cholesterol levels (e.g., familial hypercholesterolemia (FH) genes, including LDLR, APOB, PCSK9, and, less commonly, LDLRAP1, ABCG5, and ABCG8) (29). In more recent studies, the culprit mutation has been found in genes predisposing to severe forms of the metabolic syndrome (e.g., LRP6, DYRK1B) (30,31). The initial observation that supported the highly multigenic nature of CAD for a majority of subjects presenting with CAD was the failure of linkage studies performed on families with a more typical low penetrance of disease to detect any susceptibly loci (29,32).…”
Section: Linkage Studies Fail To Identify Genetic Determinants Of Commentioning
confidence: 99%
“…By selectively capturing the exons of the nearly 20,000 human genes, which constitute about 1-2 % of the euchromatic DNA, it is possible to sequence at high coverage (60-90X) the entire protein coding region of the genome at a cost of $600-800 per sample. This approach has been tremendously efficient in solving the molecular diagnosis of a multitude of Mendelian and complex traits [9][10][11][12][13][14][15][16][17][18][19][20][21]. The possibility of performing rapid diagnosis for known genetic causes for Mendelian diseases led to the development of array-based targeted gene panels for diseases (or group of diseases) to use in the clinical settings.…”
Section: Dna Sequencing and Search For Rare Variantsmentioning
confidence: 99%
“…Another study by Keramati et al also used the same method to identify a founder mutation of DYRK1B in 3 large families with coinheritance of early-onset CAD, central obesity, hypertension, and diabetes. 23 These pioneering studies highlight the opportunities of applying NGS to severely affected families to identify new mechanism of the disease and thereby new therapeutic targets.…”
Section: Whole-genome and Whole-exome Sequencing In Linkage Analysesmentioning
confidence: 99%